Identification of apple genes Md-Exp7 and Md-PG1 alleles in advanced selections resistant to scab - I. I. Suprun; S. V. Tokmakov; E. A. Al-Nakib; E. V. Lobodina (Вавиловский журнал генетики и селекции)
The creation of apple varieties with a high level of flesh firmness and long shelf life is one of the important goals in breeding. Among the genes controlling these traits, the role of the endogenous ethylene biosynthesis control gene, Md-ACS1, the expansin gene, Md-Exp7, and the polygalacturonase gene, Md-PG1, has been established. The use of DNA marker analysis to solve problems in breeding for fruit quality traits allows one not only to track several target genes simultaneously, but also to cull plants with undesirable alleles at the early stages of development. In order to select complex donors of breeding traits, molecular genetic identification of the genes that determine the quality traits of apple fruits Md-Exp7 and Md-PG1 was performed in 256 breeding selections carrying the scab resistance gene Rvi6 and valuable allelic variants of the Md-ACS-1 gene, which determines the endogenous synthesis of ethylene in fruits: 90 samples with the Md-ACS1 allele (2/2) and 166 samples with Md-ACS1 (1/2). As a result of the study, an allelic combination for the Md-Exp7 and Md-PG1 genes was established. Analysis of the parental cultivars (Renet Simirenko, Modi, Smeralda, Renoir, Fulzhion and Granny Smith) used to obtain hybrid selections revealed three alleles 198, 202, 214 bp according to the DNA marker of the Md-Exp7 gene. The SSR marker for the Md-PG1 gene amplified three alleles (289, 292, 298 bp) on the abovementioned cultivars. Within the 256 breeding selections samples that have the most priority for breeding alleles of the desired genes in combination with the Rvi6 gene and/or with selection-priority allelic variants of the Md-ACS-1 gene were identified. Of the most valuable for breeding, 46 accessions carrying the combination Md-Exp7 (202:202) + Md-ACS1 (2/2) were distinguished. Hybrids with alleles Md-PG1 (292:292) + Md-ACS1 (2/2) are also most valuable for use in breeding and as donors of selection-valuable alleles; 21 samples were identified. Accessions with a complex of breeding-valuable target alleles are valuable complex donors, as well as valuable breeding material for creating varieties with improved fruit quality characteristics and scab resistance.